FOSL1 promotes tumor growth and invasion in ameloblastoma - Xiong, Gan; Ouyang, Shengqi; Xie, Nan; Xie, Jiaxiang; Wang, Wenjin; Yi, Chen; Zhang, Ming; Xu, Xiuyun; Chen, Demeng; Wang, Cheng (Frontiers in Oncology, 2022)
Background: FOSL1, a key component of the AP-1 transcriptional complex, plays an important role in cancer cell migration, invasion and proliferation. However, the impact of FOSL1 in ameloblastoma (AM) has not been clarified. Herein, we aimed to assess the expression of FOSL1 and investigate its functional role in AM. Methods: The expression of FOSL1 was examined based on an immunohistochemistry analysis of 96 AM samples. Cell proliferation, migration, invasion and tumorigenesis were assessed by CCK8, colony formation, Transwell and sphere formation assays. RNA-seq was employed to investigate the molecular alterations of AM cells upon FOSL depletion. Microarrays of AMs were downloaded from the GEO database for bioinformatics analysis. In addition, patient-derived AM organoids were used to evaluate the therapeutic value of the AP-1 inhibitor. Results: FOSL1 was detected in the nuclei of AMs and upregulated in conventional AMs compared to unicystic AMs and normal oral epithelium. Compared with primary AM, FOSL1 expression was significantly increased in recurrent AM. Genetic knockdown of FOSL1 suppressed the proliferation, migration, invasion and sphere formation of AMs. Similar results were also observed by pharmacological inhibition of AP-1 activity. Moreover, the AP-1 inhibitor T5224 impeded the growth of organoids derived from AM patients. Mechanistically, our IPA and GSEA results revealed that depletion of FOSL1 inactivated kinetochore metaphase signaling and the epithelial-mesenchymal transition pathway and then impaired the aggressiveness of AM cells accordingly. Conclusion: FOSL1 promotes tumor recurrence and invasive growth in AM by modulating kinetochore metaphase signaling and the epithelial-mesenchymal transition pathway; thus, it represents a promising therapeutic target for AM treatment.